Semiotic Concepts of Culture and Cinema language (Journal of Philosophy, Culture and Political Science, 2024)
In this article, the authors consider one of the little-studied but pressing problems in the philosophy of culture. The purpose of this article is to study the problem of film language in the context of semiotic cultural studies. The novelty of this article topic lies in the fact that the authors analyze the place and role of signs in the formation of the language of cinema in the context of semiotic research. The theoretical and methodological basis for the study of this problem is the work of foreign, Russian, and Kazakh scientists. In the study of this problem, the authors also relied on semiotic research and also tried to apply the constructivist paradigm. While writing the article, the authors used semiotic, the method of cultural analysis and cultural-relativism, as well as such general scientific methods as analysis and generalization. This study was based on the methods of historical and cultural approach. We thought that these methods would reveal our scientific article well. As a result, the work of the director, screenwriter, sound director, and finally the game, on the one hand, and, on the other hand, the audience, construct the events taking place in the cinema and are closely associated with the world that is associated with his internal expectations, experiences, which they recreate in itself and with the world that is recreated and constructed in a certain representation of the film’s characters, and is also closely intertwined with those representations and the fictional reality created by the work of filmmakers. Every component of a film, from cultural code, sound design and acting to narrative structure and visual imagery, contributes to a semiotic fabric that reflects and refracts the complexity of human society.Key words: philosophy of culture, semiotics of culture, theory and semiotics of cinema, language, language of cinema, sign, sign-image, design features, cultural code, sound, perspective.